Métodos de fertilización y balance de nutrientes en la agricultura orgánica tradicional de la biorregión mediterránea: Cataluña (España) en la década de 1860 - Galán, Elena (2012)
To what extent were the late organic agricultures in the northwestern Mediterraneanbioregion before the green revolution sustainable? Were the soil nutrients replenished? We offerca preliminary answer to these questions by reconstructing the nutrient balance of a Catalan township circa 1861-1865. With a population density of 59 inhabitants per square kilometer, similar to other rural areas of northern Europe in that period, and a density of livestock per unit of farmland much smaller, the rural community suffered a severe shortage of manure. This gap was covered by other very labor intensive means of transferring nutrients from uncultivated areasinto farmland. Vineyards were a key element in this agro-ecosystem, because they require fewer nutrients and provided the by-product of pruning. Woodland and scrubland areas also provided significant amounts of nutrients through the collection and use of forest biomass as fertilizer.